(DE)HUMANIZATION OF PHYSICALLY DISABLED BODIES IN BORDERLANDS 3 - Anindya, Natasha Talitha; Rahmantyo, Lastiko Endi (UI Scholars Hub, 2023)
The video game industry has played a role in both affirming and erasing stereotypes surrounding minorities, especially those with disabilities. This study aims to analyse Borderlands 3’s in-game narrative that represents physically disabled characters through their characterization, visualization, and individual character development in the main plot campaign, illustrating how positive representation helps fight common stigmas and negative stereotypes. By using Shakespeare’s social model of disability as a theoretical framework, the analysis will view the game as text to identify physically disabled characters and determine if they face discrimination in the in-game universe. Results show that characters with prosthetics are considered ‘cool’ futuristic bodies symbolizing strength, while disfigured bodies still encounter discrimination with the enforcement of negative stereotypes and derogatory language. This unequal representation creates a social imbalance among physically disabled people, with the public assuming that different types of physical disabilities are superior to others.